2021
DOI: 10.1101/2021.05.27.446000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oligodendrocyte precursor cells guide the migration of cortical interneurons by unidirectional contact repulsion

Abstract: The cerebral cortex is built by neural cells that migrate away from their birthplace. In the forebrain, ventrally-derived oligodendrocyte precursor cells (vOPCs) travel tangentially together with cortical interneurons (cINs) to reach the cortex. After birth, vOPCs form transient synapses with cINs before engaging later into myelination. Here we tested whether these populations interact during embryogenesis while migrating. By coupling histological analysis of mouse genetic models with live imaging, we showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…When assembling ventral and dorsal organoids, dorsally derived oligodendroglial cells outcompete ventrally derived oligodendroglia and become dominant after long-term culture ( Kim et al, 2019 ). These results are in line with recent observations about the specific impact of ventral OPCs on the migration and maturation of mouse cortical interneurons ( Lepiemme et al, 2021 ). These pioneering studies demonstrated that generating brain organoids with myelinating OLs is indeed possible, however, they require very long protocols (from 110 to 210 days) to produce myelinated fibers.…”
Section: Brain Organoids As New Experimental Systems For In Vitro Myelination Studiessupporting
confidence: 93%
“…When assembling ventral and dorsal organoids, dorsally derived oligodendroglial cells outcompete ventrally derived oligodendroglia and become dominant after long-term culture ( Kim et al, 2019 ). These results are in line with recent observations about the specific impact of ventral OPCs on the migration and maturation of mouse cortical interneurons ( Lepiemme et al, 2021 ). These pioneering studies demonstrated that generating brain organoids with myelinating OLs is indeed possible, however, they require very long protocols (from 110 to 210 days) to produce myelinated fibers.…”
Section: Brain Organoids As New Experimental Systems For In Vitro Myelination Studiessupporting
confidence: 93%